ChemInform Abstract: 1, 5‐Benzodiazepines. Overview of Properties and Synthetic Aspects. Issue 22 (3rd June 2014) - Pareek, Aastha; Kumar, Navneet; Agarwal, Anshu; Sharma, Pratima; Kishore, Dharma
Abstract Review: 28 refs.